Decision Support System of The People's Business Credit Method Using Analytical Hierarchy Process at Bank Syariah Mandiri Kc. Lubuk Pakam - Dhini Andika; Penda Sudarto Hasugian (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Decision support system (DSS) system that can help someone in making decisions that are accurate and right on target. Many problems can be solved by using the SPK. One of them is Determining the eligibility of customers receiving the People's Business Credit (KUR). There are Several methods that can be used in building a DSS, Including Analytical Hierarchy Process (AHP). The application of the AHP method to the decision support system of people's business credit through a number of processes of data transformation starts from Determining the priority scale of each criterion, to getting the final grade and ranking. In Determining the eligibility of KUR recipient customers, there are Several criteria that are the basis for decision making, Including Credit Status, Productive Business, Business Conditions, Collateral and Collectibility.